Effects of heat-insulating glass on window penetration loss (WinPL) and building entry loss (BEL) below 40 GHz - Oh, Seongwon; Basri, Atikah Balqis; Lee, Young Chul (IEEE, 2024)
This study investigates the effects of heat-insulating glass on window penetration loss (WinPL) and building entry loss (BEL) in the 3-40 GHz range. Simulated and measured results for 12 types of glass windows, including single-, double-, and triple-glazed structures with metallic coatings, were analyzed. Thermally-efficient windows (TEW) with metallic coatings showed an average WinPL about 20 dB higher than traditional windows (TW). Both window types exhibited periodic oscillations in WinPL, and TEW demonstrating shorter periods and slight irregularities. TEW showed lower WinPL in narrow bands around 3, 5, 10, and 20 GHz. The study highlights the significant influence of WinPL on BEL, particularly in thermally-efficient buildings, and suggests the need for updated ITU-R BEL models to account for modern construction materials.